Prevalence and Associated Risk Factors for Diabetic Retinopathy among in-patients Diagnosed with Diabetes Mellitus: A Retrospective Study Conducted in Nobel Medical College and Teaching Hospital, Biratnagar - Adhikari, Bishwa Nath; Gautam, Pramod Sharma; Bekoju, Binod; Basnet, Sadhana; Bhandari, Himlal (Journal of Nobel Medical College, 2018)
Background: Diabetes mellitus (DM) being disease of modern world occurrence of Diabetic retinopathy (DR) has become more frequent. Knowledge on the prevalence and associated risk factors of diabetic retinopathy helps to detect the disease in its early course. The objective of the study was to establish the prevalence and to analyze the associated risk factors and help to screen the disease as early as possible so as to prevent and /or to delay the onset as well as progression of DR. Materials and Methods: A hospital based retrospective study conducted among 213 in-patients of Nobel Medical College, Biratnagar diagnosed with DM. Result: The prevalence of diabetic retinopathy was 32.39% and prevalence of mild NPDR, moderate NPDR, severe NPDR, very severe NPDR, proliferative diabetic retinopathy and clinically significant macular edema was 12.7%, 8.9%, 6.1%, 5%, 1.9% & 2.3% respectively. There was statistically significant relation of diabetic retinopathy with duration of diabetes (p value 0.004) and the mean duration was 8.704 years. Conclusions: The prevalence of diabetic retinopathy among in-patients was 32.39%. Though there was no significant relation with occurrence of DR with type of diabetes, age, sex, alcoholism, smoking and drug intake history, the duration of diabetes and hyperlipidemia, poor hyperglycemic control were highly significantly associated with DR while high BP showed marginally insignificant relation with the same. Journal of Nobel Medical College Volume 7, Number 1, Issue 12, January-June 2018, Page: 50-55